ANALISIS PENGARUH RELIGIUSITAS DAN KEPERCAYAAN TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN JASA KEUANGAN SYARIAH (Studi Kasus pada BMT Beringharjo Cabang Ponorogo) - Hayatul Maemunah; Mohammad Nufaiz Mauludin (Journal of Islamic Economics and Philanthropy, 2021)
Baitul Maal Wat Tamwil (BMT) is a form of non-bank sharia financial institutions whose business activities are based on the sharia system and included in (KJKS), namely sharia financial services cooperatives in Indonesia. The development of BMT in Indonesia has increased from year to year, as stated by Joelarso, General Chair of the Indonesian BMT Association Leadership Council, "until the end of 2015 there were 4,500 BMTs established in Indonesia. Seeing that the majority of people in Indonesia are Muslim, the presence of BMTs is important for the community. One of the BMTs that provide or help the economy of the community is the BMT Beringharjo Ponorogo branch that provides various services to its consumers. This study aims to examine the effect of religiosity and trust in customer decisions using the Islamic branch of BMT Beringharjo Ponorogo financial services. The population in the study was the customers of the Ponorogo branch of BMT Beringharjo with a sample of 80 respondents. Sampling uses probability sampling with simple random sampling technique, data analysis using multiple linear regression. The results showed that simultaneous Religiosity and Trust had a positive effect on Decision Making of customers at BMT Beringharjo Ponorogo. And partially (X1) Religiosity has a positive and significant effect on Decision Making. Customers use Islamic financial services at the Ponorogo branch of BMT Beringharjo, (X2) Trust has a positive and significant effect on Decision Making customers use Islamic financial services at BMT Beringharjo Ponorogo branch.